Pengaruh Keragaman Pangan, Junk Food, dan Produk Tinggi Gula Terhadap Kejadian Gizi Lebih Remaja SMAN 6 Depok: The Effect of Food Diversity, Junk Food, and High Sugar Products on The Incidence of Overnutrition in Adolescent of SMAN 6 Depok - Kencanaputri, Salma Aulia; Ilmi, Ibnu Malkan Bakhrul; Simanungkalit, Sintha Fransiske (Amerta Nutrition, 2024)
Background: The problem of overnutrition in adolescents (10-18 years) is currently quite high, >15%. Food intake is known to affect nutritional status. Consumption of diverse foods reduces the risk of overnutrition in adolescents. However, adolescents today more often consume poor food intake, such as foods high in sugar, fat, and sodium and low in fiber. It is common knowledge that they increase the risk of overnutrition. Objectives: To determine the relationship between the habit of dietary diversity, sugary food and beverages, and junk food consumption with overnutrition in adolescents. Methods: This study employed an observational analytic design with a cross-sectional approach, conducted at SMAN 6 Depok. Data analysis included univariate and bivariate analyses using the chi-square test with a 95% confidence level. The sample consisted of 112 respondents, calculated using Lemeshow's formula for the difference between two proportions and selected using stratified random sampling. Validity and reliability tests with a significance level of 0.05 have been carried out on the questionnaire before being distributed. Results: The validity test showed validity, and the reliability test showed a Cronbach Alpha value > r table (0.314). Bivariate analysis showed the adolescents did not experience overnutrition (80.4%), adolescents consumed a variety of foods (86.6%), rarely consumed sugary foods (80.4%) and sugary beverages (69.6%), and junk foods (70.5%) Conclusions: There is no significant relationship between dietary diversity, sugary food and beverages, junk food consumption, and overnutrition in adolescents.